Observing ecosystems with lightweight, rapid‐scanning terrestrial lidar scanners. Issue 4 (19th September 2016) - Paynter, Ian; Saenz, Edward; Genest, Daniel; Peri, Francesco; Erb, Angela; Li, Zhan; Wiggin, Kara; Muir, Jasmine; Raumonen, Pasi; Schaaf, Erica Skye; Strahler, Alan; Schaaf, Crystal
Abstract: A new wave of terrestrial lidar scanners, optimized for rapid scanning and portability, such as the Compact Biomass Lidar (CBL), enable and improve observations of structure across a range of important ecosystems. We performed studies with the CBL in temperate and tropical forests, caves, salt marshes and coastal areas subject to erosion. By facilitating additional scanning points, and therefore view angles, this new class of terrestrial lidar alters observation coverage within samples, potentially reducing uncertainty in estimates of ecosystem properties. The CBL has proved competent at reconstructing trees and mangrove roots using the same cylinder‐based Quantitative Structure Models commonly utilized for data from more capable instruments (Raumonen et al. 2013). For tropical trees with morphologies that challenge standard reconstruction techniques, such as the buttressed roots of Ceiba trees and the multiple stems of strangler figs, the CBL was able to provide the versatility and the speed of deployment needed to fully characterize their unique features. For geomorphological features, the deployment flexibility of the CBL enabled sampling from optimal view‐angles, including from a novel suspension system for sampling salt marsh creeks. Overall, the practical aspects of these instruments, which improve deployment logistics, and therefore data acquisition rate, are shown to be emerging capabilities, greatly increasing the potential for observation, particularly in highly temporally dynamic, inaccessible and geometrically complex ecosystems. In order to better analyze information quality across these diverse and challenging ecosystems, we also provide a novel and much‐needed conceptual framework, the microstate model, to characterize and mitigate uncertainties in terrestrial lidar observations. Abstract : This paper represents a data‐driven exploration of the applications of newly emerging rapid‐scanning, highly portable terrestrial lidar to the extraction of properties of interest in a range of important ecosystems. These studies are contextualized by a novel framework for characterizing and mitigating the instrument and ecosystem sources of uncertainty in lidar observations of structure. The necessity of quantitative information requirements and dynamic sampling for terrestrial lidar observations of ecosystem properties is established.